2003
DOI: 10.1097/01.ccm.0000085141.75513.2b
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of severe sepsis occurring in the first 24 hrs in intensive care units in England, Wales, and Northern Ireland

Abstract: Severe sepsis is common and presents a major challenge for clinicians, managers, and healthcare policymakers. Intensive care unit admissions meeting severe sepsis criteria have a high mortality rate and high resource use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
245
11
21

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(291 citation statements)
references
References 24 publications
14
245
11
21
Order By: Relevance
“…The results of our study are important for the following reasons: The prevalence of septic patients treated in the ICU was similar to that reported in other studies (16)(17)(18)(19), as well as the overall mortality. However, it was greater than that observed in some treatment arms of clinical studies (12).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The results of our study are important for the following reasons: The prevalence of septic patients treated in the ICU was similar to that reported in other studies (16)(17)(18)(19), as well as the overall mortality. However, it was greater than that observed in some treatment arms of clinical studies (12).…”
Section: Discussionsupporting
confidence: 76%
“…Several reports have confirmed that severe sepsis is found in 2% of patients admitted to the general ward, while it is found in up to 75% of ICU patients (18,20,26,27). It is logical to consider that severely ill, infected patients should be admitted to the ICU, and this can partly explain the high frequency of sepsis in the Table 4.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Severe sepsis was defined according to a modified version of the Recombinant Human Activated Protein C Worldwide Evaluation in Severe Sepsis (PROWESS) clinical trial definition. 117 Septic shock was defined as severe sepsis with cardiovascular organ system dysfunction. 118 Readmissions of women to critical care during the same hospital stay were excluded.…”
Section: Intensive Care National Audit and Research Centrementioning
confidence: 99%
“…[1][2][3][4][5] It is the 10 th most common cause of death in the United States and its management has been estimated to cost 17 billion dollars annually. 5 Among the many co-morbidities associated with increased risk for sepsis, malignancy carries one of the highest associated risks for developing sepsis and sepsis-related mortality.…”
Section: Introductionmentioning
confidence: 99%